Biocatalytic and biomimetic studies of polyphenol oxidase - Burton, Stephanie Gail (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1994)
Mushroom polyphenol oxidase (EC 1.14.18.1) was investigated to determine its potential for application as a biocatalyst in the synthesis of o-quinones, in organic medium. In order to determine the kinetic properties of the biocatalyst, a system was devised which comprised an immobilised polyphenol oxidase extract, functioning in chloroform. The system was hydrated by the addition of buffer. A simple method for the consistent measurement of reaction rates in this heterogenous system was designed and used to obtain detailed enzyme kinetic data relating to optimisation of reaction conditions and substrate specificity. The aqueous content of the system was optimised using p-cresol as a substrate. A crude, immobilised extract of Agaricus bisporus was used to hydroxylate and oxidise a range of selected p-substituted phenolic substrates, yielding, as the sale products, o-quinones. These products were efficiently reduced to catechols by extracting the reaction mixtures with aqueous ascorbic acid solution. The biocatalytic system was also successfully utilised to produce L-DOPA, the drug used to treat Parkinson's disease, from L-acetyl tyrosine ethyl ester (ATEE). Michaelis-Menten kinetics were used to obtain apparent Km and V values with respect to the selected phenolic substrates, and the kinetic parameters obtained were found to correlate well with the steric requirements of the substrates and with their hydrophobicity. In the course of the investigation, a novel Â¹H NMR method was used to facilitate measurement of the UV molar absorption coefficients of the o-quinones in reaction mixtures, thus avoiding the necessity to isolate these unstable, water-sensitive products. The biocatalytic system was extended to a continuous process, in which the immobilised enzyme was shown to function successfully in the chloroform medium for several hours, with high conversion rates. Modifications, involving partial purification and the addition of a surfactant, were investigated to determine their effect on the kinetic parameters. The results obtained using partially purified enzyme indicated that the removal of extraneous protein and/or melanoid material lead to a reduced capacity for conversion of sterically demanding substrates. The addition of the anionic detergent, sodium dodecyl sulphate (SOS), enhanced the ability of the biocatalyst to bind and oxidise sterically demanding substrates. These effects are attributed to changes in the polar state of groups within the protein binding pocket, which result in altered flexibility and hydrophobicity. Computer modelling of several biomimetic dinuclear copper complexes also indicated the importance of flexibility for effective biocatalysis. Novel binuclear copper (II complexes, containing a flexible biphenyl spacer and imidazole or benzimidazole donors, were prepared and analysed using NMR, UV, AA and cyclic voltammetric techniques. The complexes were also shown, in a detailed kinetic study, to mimic the catecholase activity of polyphenol oxidase by oxidising 3,5-di-tertbutylcatechol, and to catalyse the coupling of the phenolic substrate 2,4-di-tert-butylphenol. However, the complexes were apparently too flexible to react with smaller substrates. These biomimetic complexes provided valuable insights into the nature of the dinuclear copper binding site.
Keywords: Phenol oxidase; Polyphenols; Oxidases